The use of the particle ’ne’ in creative writing in Italian as a second language: An analysis of a Greek learners’ corpus - Florou, Katerina; Tyrou, Ioanna (Umanistica Digitale, 2024)
The analysis of learner corpora offers the possibility to retrieve recurring word strings (bigrams, trigrams, etc.) in learners’ texts. In recent decades, this method has also been used to identify lexical bundles that characterize different text genres. The aim of this study is to analyze the characteristics of recurring word sequences in texts written by students of the Department of Italian Language and Literature at the National and Kapodistrian University of Athens, in order to identify common patterns in the productions, thereby making generalizations. For this purpose, four sub-corpora of SCRICREA, a learner corpus that collects productions from students of the creative writing course, were queried through an n-gram search. The preliminary results of this process allow for a series of observations on the extracted lexical bundles. Firstly, the retrieved and analyzed lexical groups confirm that students use a limited but widespread number of prefabricated patterns. Secondly, the main cause of the few but repeated errors in the sequences can be attributed to L1 interference. These observations can have an immediate impact not only on teaching methods but also on the syllabus of Italian language teaching, as has already occurred for other languages.